Method for determination of vertical bar U(e)3 vertical bar in neutrino oscillation appearance experiments - Kajita, T.; Minakata, H.; Nunokawa, H. (Elsevier B.V., 2002)
We point out that determination of the MNS matrix element \U-e3\ = s(13) in long-baseline nu(mu) --> nu(e) neutrino oscillation experiments suffers from large intrinsic uncertainty due to the unknown CP violating phase delta and sign of Deltam(13)(2). We propose a new strategy for accurate determination of theta(13); tune the beam energy at the oscillation maximum and do the measurement both in neutrino and antineutrino channels. We show that it automatically resolves the problem of parameter ambiguities which involves delta, theta(13), and the sign of Deltam(13)(2). (C) 2002 Elsevier B.V. B.V. All rights reserved.